Exploring diet, physical activity and quality of life in females with metastatic breast cancer: a pilot study to support future intervention - Sheean, Patricia (J Acad Nutr Diet, 2015)
BACKGROUND: Historically, women with metastatic breast cancer are excluded from lifestyle interventions under the assumptions that diet and physical activity will have little impact on their disease trajectory. However, recent treatment advances have led to significant increases in survivorship that pose challenges to this assumption. OBJECTIVE: The objectives of this study were: 1) to measure dietary intake, physical functioning and quality of life (QOL) in a subset of women with metastatic breast cancer, and 2) to inform future interventions in this growing population. DESIGN: Demographics, clinical characteristics, dietary intake, physical functioning and QOL were examined cross-sectionally using validated methodologies. PARTICIPANTS/SETTING: Twenty-five women with metastatic breast cancer were recruited over a 4 month period (June-September, 2014) from two university hospitals in the Midwest that serve an ethnically diverse patient population. Women completed questionnaires and 24-hour dietary recalls (one weekday, one weekend). MAIN OUTCOME: Lifestyle habits were analyzed. STATISTICAL ANALYSES: Means (± standard deviations) and frequencies were tallied and t-tests were conducted. RESULTS: On average, participants were 58.8 (± 12.8) years of age, predominantly minority, had been living with metastatic breast cancer for an average of 36.9 (± 29.3) months, and exhibited significant nutrition impact symptomology (e.g, pain, dry mouth, fatigue.) Bone and lung were the most common sites of metastases. Compared to a larger, normative sample of women with metastatic breast cancer, study participants displayed similar physical (p=0.61) and functional well-being scores (p=0.76), but higher social (p=0.10) and emotional well-being scores (p<0.01). The analyses of lifestyle factors showed that the majority of women were overweight or obese (n=14), not routine exercisers (n=15) and had dietary patterns high in fat and low in fiber. CONCLUSIONS: This study supports that many women with metastatic breast cancer are in need of carefully tailored, evidence-based lifestyle strategies that address symptom burden, including weight management. The implications of diet and physical activity on QOL in this population remain unexplored.